Variability in antenatal prognostication of fetal diaphragmatic hernia across the North American Fetal Therapy Network (NAFTNet). (8th December 2019) - Abbasi, Nimrah; Cortes, Magda Sanz; Ruano, Rodrigo; Johnson, Anthony; Morgan, Tara; Coleman, Beverly; Baschat, Ahmet; Zaretsky, Michael; Lim, Foong Yen; Bulas, Dorothy; Benachi, Alexandra; Ryan, Greg; et al.
Abstract: Objective: To evaluate variability in antenatal sonographic prognostication of congenital diaphragmatic hernia (CDH) within the North American Fetal Therapy Network (NAFTNet). Methods: NAFTNet centre were invited to complete a questionnaire and participate in videoconference calls, during which participants were observed while measuring lung area by ultrasound using the anteroposterior (AP) method, longest method, and trace method. Each center identified 1–2 experienced fetal medicine specialist(s) or medical imaging specialists locally to participate in the study. Practices were compared among NAFTNet centre within and without the fetal endoscopic tracheal occlusion (FETO) consortium. Results: Nineteen participants from 9 FETO center and 30 participants from 17 non‐FETO center completed the survey and 31 participants were interviewed and observed while measuring sonographic lung area. All Centres measured observed‐to‐expected lung‐to‐head ratio (o/e LHR) or LHR for CDH prognostication. Image selection criteria for lung area measurement were consistent, including an axial section of the chest with clear lung borders and a 4‐chamber cardiac view. Lung area measurement methods varied across NAFTNet, with most centre using longest (4/9 FETO vs. 13/29 non‐FETO) or trace (3/9 FETO vs. 11/29 non‐FETO) method. Centres differed in expected reference ranges for o/e LHR determination and whether the lowest, highest or average o/e LHR was utilized. Conclusion: Variability in antenatal sonographic prognostication of CDH was identified across NAFTNet, indicating a need for consensus‐based standardization.